Thermodynamics of second-grade nanofluid over a stretchable rotating porous disk subject to Hall current and cubic autocatalysis chemical reactions - Khan, Noor Saeed; Fernandez-Gamiz, Unai; Khan, Muhammad Sohail; Kumam, Wiyada; Kumam, Poom; Galal, Ahmed M. (Frontiers in Physics, 2022)
Homogeneous–heterogeneous chemical reactions for second-grade nanofluid and gyrotactic microorganisms in a rotating system with the effects of magnetic fields and thermal radiation are examined. The boundary layer equations of the problem in a non-dimensional form are evaluated by a strong technique, namely, the homotopy analysis method (HAM). The rates of flow, heat, mass, and gyrotactic microorganism motion are obtained for the augmentations in the pertinent parameters. The graphical pictures of the results are described by the physical significance. The Hall current effect decreases the azimuthal velocity, the axial velocity increases with the injection of mass, the Biot number leads to enhanced heat transfer and gyrotactic microorganisms, the concentration diffusion rate decreases with the Peclet number, and the concentration of the chemical reaction reduces with the Schmidt number. Excellent agreement of the present work is found with the previously published work. The present study has applications in the hydromagnetic lubrication, semiconductor crystal growth control, austrophysical plasmas, magnetic storage disks, computer storage devices, care and maintenance of turbine engines, aeronautical, mechanical, and architectural engineering, metallurgy, polymer industry, hydromagnetic flows in porous media, and food processing and preservation processes.